The length of a lantibiotic hinge region has profound influence on antimicrobial activity and host specificity - Zhou, Liang; van Heel, Auke J.; Kuipers, Oscar P. (Frontiers in Microbiology, 2015)
Lantibiotics are ribosomally synthesized (methyl)lanthionine containing peptides which can efficiently inhibit the growth of Gram-positive bacteria. As lantibiotics kill bacteria efficiently and resistance to them is difficult to be obtained, they have the potential to be used in many applications, e.g. in pharmaceutical industry or food industry. Nisin can inhibit the growth of Gram-positive bacteria by binding to lipid II and by making pores in their membrane. The C-terminal part of nisin is known to play an important role during translocation over the membrane and forming pore complexes. However, as the thickness of bacterial membranes varies between different species and environmental conditions, this property could have an influence on the pore forming activity of nisin. To investigate this, the so-called “hinge region” of nisin (residues NMK) was engineered to vary from one to six amino acid residues and specific activity against different indicators was compared. Antimicrobial activity in liquid culture assays showed that wild type nisin is most active, while truncation of the hinge region dramatically reduced the activity of the peptide. However, one or two amino acids extensions showed only slightly reduced activity against most indicator strains. Notably, some variants (+2, +1, -1, -2) exhibited higher antimicrobial activity than nisin in agar well diffusion assays against Lactococcus lactis MG1363, Listeria monocytogenes, Enterococcus faecalis VE14089, Bacillus sporothermodurans IC4 and Bacillus cereus 4153 at certain temperatures.